Identification and role of CmLhcb2.1 in regulating low-light stress resistance in Chinese chestnut (Castanea mollissima) - Yang, Yong; Wang, Xuan; Liu, Jing; Wang, Meng; Yu, Liyang; Wang, Dongsheng; Li, Jingshi; Lu, Yi; Zhang, Jingzheng; Zhang, Haie (Frontiers in Plant Science, 2025)
Chinese chestnut (Castanea mollissima) is a significant woody food plant that has garnered increasing attention due to its potential role in addressing food security challenges. However, low yield remains a critical issue facing the Chinese chestnut industry. One contributing factor to this low yield is insufficient light, particularly since Chinese chestnuts predominantly grow in mountainous regions. Therefore, the present study aims to investigate the intrinsic mechanisms underlying chestnut resistance to light stress, identify and validate genes associated with low light stress tolerance, and provide a foundation for targeted breeding of chestnut varieties that can withstand light stress. Studies have demonstrated that the light-harvesting chlorophyll a/b (Lhca/b) proteins play key roles in regulating the adaptation of plants to low-light stress. However, there have been no reports on the role of the Lhca/b gene family in the chestnut under light stress. We initially identified 17 CmLhca/b gene members across the chestnut genome and constructed a phylogenetic tree that divided them into five subgroups: the Lhca, the Lhcb, the CP24, the CP26, and the CP29 groups. CmLhcb2.1 and CmLhcb2.2 were grouped on the same branch with GhLhcb2.3 of upland cotton that involved in chlorophyll synthesis.The chestnut leaves exhibited phenotypic and transcriptomic differences under low and normal light conditions. By the 10th day of shading treatment, the leaves showed signs of damage, with the extent of damage intensifying as shading intensity increased. Additionally, the leaf color darkened due to the gradual increase in chlorophyll b content, which was correlated with increased shading intensity. The gene CmLhcb2.1 was upregulated across all shading intensities. Specifically, quantitative reverse transcription PCR (qRT-PCR) confirmed the upregulation of CmLhcb2.1 in chestnut under low-light stress. Overexpression studies in tobacco indicated that CmLhcb2.1 enhances chestnut resistance to low-light stress by promoting chlorophyll b synthesis. Finally, yeast one-hybrid and dual-luciferase reporter assays confirmed that the transcription factor CmGLK positively regulated CmLhcb2.1. These findings lay a theoretical foundation for exploring how CmLhcb2.1 regulates chestnut resistance to low-light stress.